Analisis Pengaruh Citra Merek, Promosi, Kualitas Pelayanan Terhadap Kepuasan Konsumen Ritel - Nasrul Efendi; Tya Wildana Hapsari Lubis (Jurnal Wira Ekonomi Mikroskil, 2022)
The purpose of this research is to see the contribution of brand ideals, promotions and service quality to customer satisfaction at Brastagi Supermarket. This research is an associative research, namely research that provides an overview of the relationship and influence of two or more variables. The research population came from consumers of Brastagi Supermarket with a sample of 167 respondents. The sampling technique used a non-probability sampling technique with a accidental sampling approach, namely the researcher chose the sample subjectively. Data analysis was carried out with SPSS software. From the results of the study concluded that brand image and service quality partially affect consumer satisfaction, while promotion does not partially affect customer satisfaction. Then, together, brand image, promotion and service quality can influence consumer satisfaction with a coefficient of determination (R²) 56.2 indicating that brand image, promotion and service quality are only able to explain consumer satisfaction by 56.2% while 43 ,8,4% explained by other variables. Suggestions for continued research that aims to determine other variables that play a role in realizing customer satisfaction, should be expanded by adding other variables such as store atmosphere, product quality and price.